Efficient solid-state dye sensitized solar cells: The influence of dye molecular structures for the in-situ photoelectrochemically polymerized PEDOT as hole transporting material. (January 2016) - Zhang, Jinbao; Vlachopoulos, Nick; Jouini, Mohamed; Johansson, Malin B.; Zhang, Xiaoliang; Nazeeruddin, Mohammad Khaja; Boschloo, Gerrit; Johansson, Erik M.J.; Hagfeldt, Anders
Abstract: Solid-state dye sensitized solar cells (sDSCs) with organic small molecule hole transporting materials (HTMs) have limited efficiencies due to the incomplete pore filling of the HTMs in the thick mesoporous electrodes and the low hole conductivity of HTMs. Hereby, highly efficient sDSCs with power conversion efficiency of 7.11% and record photocurrent of 13.4 mA cm − 2 are reported, prepared by effectively incorporating in-situ photoelectrochemically polymerized PEDOT as HTM in combination with a multifunctional organic, metal-free dye. In order to fundamentally understand how the dye molecules affect the photoelectrochemical polymerization (PEP), the properties of the generated PEDOT and the photovoltaic performance, sDSCs based on a series of dyes are systematically investigated. Detailed comparative studies reveal that the difference between the dye redox potential and monomer onset oxidation potential plays a crucial role in the PEP kinetics and the doping density of PEDOT HTM. The structure of the dyes, functioning as an electron blocking layer, affects the charge recombination at the TiO2 /dye/PEDOT interface. The analysis shows that a donor-π-acceptor dye with well-tuned energy levels and bulky structure results in an in-situ electrochemically doped PEDOT HTM with a high hole conductivity (2.0 S cm − 1 ) in sDSCs, leading to efficient dye regeneration and photocharge collection. It is hoped that this work will further encourage research on the future design of new dye molecules for an efficient PEP in order to further enhance the photovoltaic performance of solid-state dye sensitized solar cells. Graphical abstract: In-situ photoelectrochemical polymerization approach is employed to deposit conducting polymer PEDOT hole conductor for solid-state dye sensitized solar cells. A high efficiency of 7.11% with record photocurrent (13.4 mA cm −2 ) is reported by efficient utilization of a multifunctional dye LEG4 to generate an in-situ electrochemically doped PEDOT HTM and thus highest hole conductivity of 2.0 S cm −1 ever reported in sDSCs, leading to efficient charge collection in devices. Highlights: Energy efficiency of 7.1% for dye solar cells with photopolymerized hole conductor. Important effect of dye structure and energy levels on properties of hole conductor. Highest hole conductivity 2.0 S/cm in dye solid-state solar cells with dye LEG4. High photocurrent13 mA/cm 2 due to high collection efficiency and lowrecombination.